Phylogenetic relatedness rather than aquatic habitat fosters horizontal transfer of transposable elements in animals - Muller, Héloïse; Savisaar, Rosina; Peccoud, Jean; Charlat, Sylvain; Gilbert, Clément (Genome Research, 2025)
Horizontal transfer of transposable elements (HTT) is an important driver of genome evolution, yet the factors conditioning this phenomenon remain poorly characterized. Here, we screen 247 animal genomes from four phyla (annelids, arthropods, mollusks, chordates), spanning 19 independent transitions between aquatic and terrestrial lifestyles, to evaluate the suspected positive effects of aquatic habitat and of phylogenetic relatedness on HTT. Among the 6043 independent HTT events recovered, the vast majority (>85%) involve DNA transposons, of which Mariner-like and hAT-like elements have the highest rates of horizontal transfer and of intragenomic amplification. Using a novel approach that circumvents putative biases linked to phylogenetic inertia and taxon sampling, we find that HTT rates positively correlate with similarity in habitat type but are not significantly higher in aquatic than in terrestrial animals. However, modeling the number of HTT events as a function of divergence time in a Bayesian framework reveals a clear positive effect of phylogenetic relatedness on HTT rates in most of the animal species studied (162 out of 247). The effect is very pronounced: A typical species is expected to show 10 times more transfers with a species it diverged from 250 million years (My) ago than with a species it diverged from 650 My ago. Overall, our study underscores the pervasiveness of HTT throughout animals and the impact of evolutionary relatedness on its dynamics.